Photo-geology of the Montefalco Quaternary Basin, Umbria, Central Italy. Issue 1 (4th November 2016) - Bucci, Francesco; Mirabella, Francesco; Santangelo, Michele; Cardinali, Mauro; Guzzetti, Fausto
ABSTRACT: We present a photo-geological map for the 185 km 2 fault-bounded, Montefalco Basin, Umbria, Central Italy. The basin formed in the Quaternary in response to extensional tectonics dissecting folds and thrusts of the northern Apennines range. To prepare the 1:25, 000 geological map, we integrated geological and morphological information obtained through the visual analysis of three sets of aerial photographs of different age, the collection of new field data, and the review of pre-existing surface and sub-surface geological data. We show that systematic interpretation of aerial photographs contributed to improving the geological mapping, providing information not readily available through traditional field mapping. We expect that the new map will be used for different types of geological and geomorphological investigations, including studies of active tectonic, Quaternary morpho-tectonics, sedimentological and stratigraphic analyses, mining and exploration investigations, and the analysis of landslide types, patterns and distribution.